Performance feedback, financial slack and the innovation behavior of firms - Lu, Lin-Hua (Springer Nature, 2020)
Building on Cyert and March’s(1963) behavioral theory of the firm, we investigate how firms adjust their exploratory and exploitative innovation activities in response to performance feedback, and how this adjustment is moderated by the firms’ financial slack. We find that firms invest in a different mix of innovation activities when they receive positive versus negative performance feedback. Specifically, our empirical results show that the higher a firm’s performance is above its aspiration level, the lower will be the share of exploratory innovation in its total portfolio of innovation activities. In contrast, the lower a firm’s performance is below its aspiration level, the higher will be the share of exploratory innovation in its total innovation activities. While financial slack has the direct effect of increasing the share of exploratory innovation activities, its interaction with performance feedback appears to moderate this effect when the firm is underperforming.